Discordance of global assessment between the patients and physicians predicts 9-year pain-related outcomes in rheumatoid arthritis patients - Hayashi, Kazuhiro; Miki, Kenji; Shi, Kenrin; Yukioka, Masao; Hirayama, Takehiro; Tsujimoto, Kohei; Takeuchi, Takao; Hayaishi, Yasuhisa; Hayaishi, Masahiro (Frontiers in Medicine, 2023)
Introduction: Perspectives regarding the disease state often differ between patients with rheumatoid arthritis (RA) and physicians. The aim of the present longitudinal cohort study was to investigate the impact of the discordance in global assessments between patients and physicians on 9-year pain-related outcomes in patients with rheumatoid arthritis. Method: Sixty-eight consecutive outpatients with rheumatoid arthritis on their first visit to a tertiary center were included. Baseline measurements included demographic data, drugs used, disease activity, and a modified Health Assessment Questionnaire (mHAQ). Discordance in global assessment between patients and physicians at baseline was defined as 10 mm higher in the patient global assessment (PGA) than in the physician global assessment. A 9-year follow-up assessment included pain intensity, the Euro Quality of life-5 Dimensions-3 level (EQ-5D-3L) scale, Pain Catastrophizing Scale, Hospital Anxiety and Depression Scale, Pain Disability Assessment Scale, and Pain Self-Efficacy Questionnaire. Results: The number of patients with discordance was 26 (38%) in 68 patients. Patients with a 10 mm PGA higher than the physician global assessment at baseline measurements had significantly worse pain intensity, Pain Catastrophizing Scale score, Pain Self-Efficacy Questionnaire score, and EQ-5D-3L score at the 9-year follow-up measurements than those with concordance. A higher mHAQ score and 10 mm PGA higher at baseline were significantly independently associated with the EQ-5D-3L scale score and pain intensity at the 9-year follow-up. Conclusions: This longitudinal cohort study suggested that discordance in global assessment between patients and physicians modestly predicted worse 9-year pain-related outcomes in patients with rheumatoid arthritis.